2017
DOI: 10.37190/epe170320
|View full text |Cite
|
Sign up to set email alerts
|

Local community e-waste awareness and behavior. Polish case study

Abstract: Waste awareness and behavior of local Polish community has been examined. Specifically, the issue of selective waste electrical and electronic equipment (WEEE) collection has been explored. The main objectives of the research was to evaluate an attitude of the individuals towards e-waste treatment and to recognize the causes of low efficiency of the current WEEE management. The research was conducted among the inhabitants of a small town in Poland. Collected data may be useful while preparing household WEEE ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, the distance extended to 150 km, which confirmed the findings of Kołsut's study regarding the distances between the bodies involved in processing and collecting waste in Poland (Kolsut, 2016). A remarkable increase in the distances for waste transportation to disposal facilities was also observed (Pasiecznik et al, 2017;Zemanek et al, 2011).…”
Section: Spatial Interactions In the Volume Of Municipal Wastementioning
confidence: 71%
“…However, the distance extended to 150 km, which confirmed the findings of Kołsut's study regarding the distances between the bodies involved in processing and collecting waste in Poland (Kolsut, 2016). A remarkable increase in the distances for waste transportation to disposal facilities was also observed (Pasiecznik et al, 2017;Zemanek et al, 2011).…”
Section: Spatial Interactions In the Volume Of Municipal Wastementioning
confidence: 71%
“…Due to lack of knowledge, informal sector collectors and recyclers got an advantage and became more influential. For example, Islam et al (2016) found that 30% of the households preferred to sell their e-waste items to local scrap collectors or even throwing e-waste with household waste, as indicated by Pasiecznik et al (2017)'s study in which 12% of respondents (mostly young consumers) did so. For a formal system (developed and prepared as per environmental guidelines), 'weak environmental protection awareness' and limited knowledge of recycling channels results in a low collection rate, which is a loss in investment.…”
Section: Lack Of E-waste-related Awarenessthe Consequencesmentioning
confidence: 99%
“…Other notable methods of e-waste disposal include -"throwing e-waste with household solid waste/mixed waste" (Arain et al, 2020, Araujo et al, 2017, Blake et al, 2019, Borthakur and Govind, 2019, Bovea, M.D. et al, 2018, Chi et al, 2014, Fraige et al, 2012, Gök et al, 2017, Martinho et al, 2017, Pasiecznik et al, 2017, Rodrigues et al, 2020, Wieser and Tröger, 2018, "donate to others" (Abbondanza and Souza, 2019, Araujo et al, 2017, Borthakur and Govind, 2019, Cao et al, 2016, Colesca et al, 2014, Echegaray, 2016, Fraige et al, 2012, Hamdan and Saidan, 2020, Martinho et al, 2017, Rodrigues et al, 2020, "drop it to council collection centers/recycling centers" (Araujo et al, 2017, Borthakur and Govind, 2019, Chi et al, 2014, Fraige et al, 2012, Martinho et al, 2017, Rodrigues et al, 2020, Wieser and Tröger, 2018, "selling" (Cai et al, 2020, Cao et al, 2016, Chi et al, 2014, Echegaray, 2016, Fraige et al, 2012, Hamdan and Saidan, 2020, Nguyen et al, 2009, Ongondo and Williams, 2011, Ravindra and Mor, 2019…”
Section: Mode Of Disposalmentioning
confidence: 99%
“…WEEE contains many different hazardous components that can be released during improper storage or processing, posing a threat to human health and the environment [ 8 ], as well as valuable precious metals, such as gold or silver, the recovery of which is desirable [ 7 , 8 , 9 , 10 ]. For example, conductive elements of printed circuit boards include, among others, gold, silver, tin, and zinc [ 11 , 12 ]. Therefore, the development of methods for reducing of the amount of electronic scrap—enabling its reuse, recycling, and various forms of recovery—is extremely important not only for the protection of the natural environment (energy saving, reduction of water and air pollution), but also for economic reasons [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are of great interest and will probably play a key role in the management of waste electronic and electrical equipment in the future [ 18 , 20 ]. However, such recovery processes are usually complex, and they involve many unit operations, ranging from disassembly, grinding, and physical separation of components to leaching, which leads to the transfer of the desired substances into aqueous solutions, followed by extraction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%